Les Sepultures dels bisbes de Vic (dels necrologis i obituaris als epitafis) - Ordeig i Mata, Ramon (Miscel·lània litúrgica catalana, 2014)
The necrologies and obituaries of Vic Cathedral, as well as other funerary documents, contain information not only about decessions of the Bishops of this see during Medieval and Modern times, but also about their funerals and tombs. The data about the tombs are particularly interesting because, due to the demolition of the Romanesque cathedral, the most ancient preserved episcopal tombs are nowadays the Baroque urn of saint Bernat Calbó and the three tombs from the 18th century located in the same chapel. The epitaphs transcribed in the old episcopologies are an additional information source, previous to that offered by the epitaphs in the extant tombs.